Pemberdayaan Masyarakat melalui Turnamen Sepak Takraw Berbasis UMKM di Nagari Sikucur - Novita Efendi; Annisa Annisa; Dhita Salsabila; Rahmat Pambudi; Naja Klaudia; Febryan Anggara Syahputra Pratama (Bumi: Jurnal Hasil Kegiatan Sosialisasi Pengabdian kepada Masyarakat, 2026)
This community service activity aims to describe the process and impact of the UMKM-Based Sepak Takraw Tournament for all of West Sumatra (Piala Limkos Sedunia) held in Nagari Sikucur, V Koto Kampung Dalam District, Padang Pariaman Regency, West Sumatra, as part of the Regular KKN Program of Universitas Negeri Padang for the January–February 2026 period. The method used is participatory action research with a qualitative descriptive approach. Activities were carried out for 30 days (January 9–February 8, 2026), involving 32 teams from 19 districts/cities across West Sumatra and hundreds of local UMKM actors. KKN students served as media partners, live streaming hosts on social media, and documentation committees. Results indicate that the tournament successfully stimulated the local economy with significant financial turnover through a 14-day UMKM bazaar, increased promotion of traditional sepak takraw sports, and strengthened social cohesion among nagari residents. The activity also contributed as an athlete development platform ahead of the West Sumatra Provincial Sports Week (PORPROV) 2028. The integration of sport events with UMKM empowerment has proven to be an effective strategy for improving rural community welfare.